Studi Kualitas Fisis Air Sungai Leang Lonrong Kawasan Karst Pangkep Taman Nasional Bantimurung Bulusaraung: Studi Kualitas Fisis Air Sungai Leang Lonrong - Aslami, Rindah Putri; Arsyad, Muhammad; Sulistiawaty, Sulistiawaty (Progressive Physics Journal, 2024)
This research is an experimental research with a survey type aimed to analyse water quality of the Leang Lonrong River reviewed from smell, taste, Total Dissolved Solid (TDS), turbidity, temperature, color, clarity, and UV index, as well as to describe community activities as factors that influence the water quality of the Leang Lonrong River in its utilization. This study was carried out in the Region Tour Leang Lonrong in the Panaikang Village, Minasatene District, Pangkep Regency, which is one of part Pangkep Karst Area Bantimurung Bulusaraung National Park. In the study, the measurement of water quality for sanitary hygiene needs and public bath reviewed its physical parameters by Regulation Minister Health No. 32 of 2017. Obtained results study that physical parameters water of Leang Lonrong River for sanitary hygiene needs own quality that meets requirement, because the water no smells, no taste, has an average TDS of 6.44 mg/L, an average turbidity of 1.71 NTU, an average temperature of 24.14 °C, and average color 0 TCU. The water of Leang Lonrong River for necessity public bath is no fulfill appropriate water quality standard raw quality. This caused some parameters not to fulfill the standard, namely the parameter of clarity is an average of 0.136 meters deep and UV index parameters more than 3 on at 11:00 a.m and 1:00 p.m in Central Indonesia Time (WITA).